Service System Design Utilizing a Service Science Perspective: Case of Pijar Mahir Digital Education Platform (The Indonesian Journal of Business Administration, 2021)
Indonesia has made significant progress on improving education access in the last few years. One of the leading telecommunication and technology company see the need to deliver competitive advantage into this sector through digital education platform technology business unit. The current service design of digital education platform has several problems, first is the infectivity of content delivery and second is the gap between value proposed and value perceived. Through external analysis of PESTEL and SWOT, internal analysis of service blueprint and lean canvas, the author deliver solutions for digital education platform technology through the perspective of service science in a form of new service blueprint and value co-creation activity based on the value orchestration strategy. The findings of this study show that to increase the effectivity of the service delivery and reduce the gap between value proposed by Pijar Mahir and value perceived by its customer, there are several improvements of the service needed. First is the addition of question-and-answer features of content delivery. Second is the improvement of content delivery method through case study and virtual tutoring. Third is the addition of customer service real time chat. Fourth is the improvement of rating questionnaire for related content.Keywords: Service Science, Value Co-Creation, Value Orchestration, Service Blueprint, Digital Education Platform